Education Support And Environment Protection (2020)
Education at an early age should represent an important point in the social responsibility that industrial designers have. This document contributes to this objective under the concept of reuse, in order to take advantage of available resources and reduce consumption rates. After raising the problem and collecting the information required during the fieldwork at the Indalecio Penilla Educational Institution, Manuela Beltrán campus (Cartago, Valle), existing typologies on children’s furniture and recreational-pedagogical elements were analyzed, viable design alternatives were projected and they were selected according to a matrix created under the design requirements. The proposed solution is responsible with the environment and supports the improvement of educational quality within the classroom.